2017
DOI: 10.5194/bg-14-4045-2017
|View full text |Cite
|
Sign up to set email alerts
|

Isoprenoid emission response to changing light conditions of English oak, European beech and Norway spruce

Abstract: Abstract. Light is an important environmental factor controlling biogenic volatile organic compound (BVOC) emissions, but in natural conditions its impact is hard to separate from other influential factors such as temperature. We studied the light response of foliar BVOC emissions, photosynthesis and stomatal conductance on three common European tree species, namely English oak (Quercus robur), European beech (Fagus sylvatica) and two provenances of Norway spruce (Picea abies) in Taastrup, Denmark. Leaf scale … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…As expected [31,34,[39][40][41], isoprene increased with increasing PAR levels. Studies have also shown that the emission rates of isoprene have a hyperbolic relationship with PAR [34,40,42,43].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As expected [31,34,[39][40][41], isoprene increased with increasing PAR levels. Studies have also shown that the emission rates of isoprene have a hyperbolic relationship with PAR [34,40,42,43].…”
Section: Discussionsupporting
confidence: 83%
“…The sample cartridges were filled in a 2-bed configuration with Tenax TA (porous organic polymer) and Carbograph 1TD (graphitized carbon black) adsorbents. Similar set-ups had been used in other studies before [26,[29][30][31].…”
Section: Methodsmentioning
confidence: 99%
“…Besides the branch chamber, a portable photosynthesis system (LI-6400XT, LI-COR, NE, USA) was used in 2016 to provide photosynthesis information in parallel with BVOC measurements from individual Salix leaves [42,46,50,52]. The leaf chamber has a capacity to measure leaves with an area up to 6 cm 2 (2 × 3 cm 2 ) and the measurements were done on the middle part of the leaves to obtain the maximum area of the leaves.…”
Section: Light Response Curves and Photosynthesis Ratesmentioning
confidence: 99%
“…Air from the dynamic chamber was pulled through an adsorbent cartridge for 20 min per sample at a flow rate of 200 mL min −1 using a flow-controlled pump (Pocket Pump, SKC Ltd., Dorset, UK), leading to a total sample volume of 4 L. In the case of the leaf chamber, the photosynthesis system had been modified with a trace-gas tube connection after the outlet of the leaf chamber [42,46,50,52]. This way, BVOC samples could be taken in parallel to the on-going photosynthesis measurements.…”
Section: Bvoc Samplingmentioning
confidence: 99%
See 1 more Smart Citation